Perbandingan Bunyi Fonem dalam Bahasa Sunda dan Bahasa Indonesia - Destiani, Destiani; Restiana, Dina; Aqilah, Khansa Zahra; Abdhiya, Muhammad Shidqy; Jadie, Amjad Ali; Guna, Irga Wijaya (STKIP PGRI Ponorogo Press, 2026)
This study aims to determine the differences in phoneme sounds between Sundanese and Indonesian. Phonemes are the smallest units of sound. This study aims to explain and show examples of vocabulary in Sundanese and Indonesian that have the same meaning, but different phonemes. This study uses a qualitative descriptive method comparing Sundanese and Indonesian phonemes. The results show that there are 7 vowel phonemes in Sundanese, while in Indonesian there are 5. There are 18 consonant phonemes in Sundanese, while in Indonesian there are 21. This is due to the existence of several special phonemes in the way of writing, pronunciation, or how phonemes are used in Indonesian and Sundanese. With this study, it is hoped that it can provide data that shows the differences in phoneme sounds in Indonesian and Sundanese.